2011
DOI: 10.3928/00220124-20110516-03
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Professional Practice and Work Environment of New Graduates in a Nurse Residency Program

Abstract: New nurses continue to face challenging work environments and high expectations for professional competence as they enter practice. Nurse residency programs are gaining prominence as a mechanism to ease new graduates’ transition to practice. This study examined new graduates’ perceptions of their professional practice competence and work environment throughout a yearlong nurse residency program. Employing a repeated measures design, data were collected at baseline, at 6 months, and at 12 months. Results showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 35 publications
2
46
0
Order By: Relevance
“…These findings are consistent with existing nursing research. Nursing residency programs have contributed significantly to new graduate nurses' development and improvement in their competencies, specifically clinical decision making (AL-Dossary et al, 2014;Bratt, 2009Bratt, , 2013Bratt & Felzer, 2011Casey et al, 2004;Goode et al, 2009;Kowalski & Cross, 2010;Messmer, Jones, & Taylor, 2004;Roud et al, 2005;Williams, Goode, Krsek, Bednash, & Lynn, 2007). In this study the new graduate nurses' perceptions of clinical decision-making had improved by the end of their residency program, which provides critical evidence that residency programs can enhance new graduates' CDM abilities (Bratt & Felzer, 2011).…”
Section: Discussion Of Findingsmentioning
confidence: 78%
See 2 more Smart Citations
“…These findings are consistent with existing nursing research. Nursing residency programs have contributed significantly to new graduate nurses' development and improvement in their competencies, specifically clinical decision making (AL-Dossary et al, 2014;Bratt, 2009Bratt, , 2013Bratt & Felzer, 2011Casey et al, 2004;Goode et al, 2009;Kowalski & Cross, 2010;Messmer, Jones, & Taylor, 2004;Roud et al, 2005;Williams, Goode, Krsek, Bednash, & Lynn, 2007). In this study the new graduate nurses' perceptions of clinical decision-making had improved by the end of their residency program, which provides critical evidence that residency programs can enhance new graduates' CDM abilities (Bratt & Felzer, 2011).…”
Section: Discussion Of Findingsmentioning
confidence: 78%
“…Age, overall GPA, and enrollment in a residency program were the primary variables in this study since in the nursing literature it was found that they predict clinical decisionmaking skills (AL-Dossary et al, 2014: Bratt, 2013Bratt & Felzer, 2011Higuchi & Donald, 2002;Oermann & Garvin, 2002;Siew Eng et al, 2011;Torunn Bjørk & Hamilton, 2011). Although marital status has been found to shown…”
Section: Methodsmentioning
confidence: 95%
See 1 more Smart Citation
“…17,18 These results are supported in a longitudinal study where newly licensed nurses reported greatest levels of job satisfaction, retention and work ability, and lowest levels of stress at one year after employment. 19 Interestingly, both nurses and certified nursing assistants presented a drop of job satisfaction at six months after their employment start date. 19,20 These two longitudinal studies, however, present response bias with the use of the same survey at each test point, and 66% attrition before the 1 year test point.…”
Section: Cognitivementioning
confidence: 99%
“…19 Interestingly, both nurses and certified nursing assistants presented a drop of job satisfaction at six months after their employment start date. 19,20 These two longitudinal studies, however, present response bias with the use of the same survey at each test point, and 66% attrition before the 1 year test point. 19,20 Job satisfaction, retention, and work ability scores were also reported greater after a continuing education seminar for a small sample (n = 47) of certified nursing assistants.…”
Section: Cognitivementioning
confidence: 99%